Meta-analysis of the efficacy and safety of non-vitamin K antagonist oral anticoagulants with warfarin in Latin American patients with atrial fibrillation. Issue 18 (May 2020) - Su, Zhiyu; Zhang, Hao; He, Wenfeng; Ma, Jianyong; Zeng, Junquan; Jiang, Xinhua
Abstract: Background: Data of non-vitamin K antagonist oral anticoagulants (NOACs) in current management of atrial fibrillation (AF) are predominantly derived from North American and European regions. However, the effects of NOACs for stroke prevention in Latin America remain unclear. Therefore, we aimed to compare the efficacy and safety of NOACs with warfarin in Latin American patients with AF. Methods: The PubMed and Embase databases were systematically searched until July 12, 2019 for applicable randomized clinical trials. The risk ratios (RRs) and 95% confidence intervals (CIs) were pooled using a random-effects model. Results: Four trials involving 8943 Latin American patients were included in this meta-analysis. In anticoagulated patients with AF, Latin American patients had higher rates of stroke or systemic embolism and all-cause death compared with non-Latin American subjects. Compared with warfarin use, the use of NOACs was significantly associated with reduced risks of stroke or systemic embolism, major bleeding, intracranial bleeding, and any bleeding in Latin American patients. There were no significant differences in the risks of ischemic stroke, all-cause death, and gastrointestinal bleeding between Latin and non-Latin American groups. All the interactions between Latin and non-Latin American groups about efficacy and safety outcomes of NOACs compared with warfarin were non-significant (all P interaction > .05). Conclusions: Our meta-analysis suggested that the use of NOACs was at least non-inferior to warfarin use for stroke prevention in Latin American patients with AF. Abstract : Supplemental Digital Content is available in the text